Understanding the Effects of Deep Space Radiation on Nervous System: The Role of Genetically Tractable Experimental Models - Onorato, Giada; Di Schiavi, Elia; Di Cunto, Ferdinando (Frontiers in Physics, 2020)
Space agencies are working to establish a permanent human presence on the moon and to reach Mars within the next few decades. In these missions, astronaut crew members will be exposed to moderate doses of the highly energetic particles that compose galactic cosmic rays (GCR). GCR consist of alpha particles, protons, and high atomic number ions, stripped of their electrons (HZE), which are relatively rare, but are also highly ionizing. HZE are particularly damaging to biological tissues, because they can penetrate to much deeper layers of shielding materials than gamma rays and x-rays and produce within tissues long ionization tracks, with strongly clustered damage to information molecules. The consequences of such damage to central nervous system health is a major concern. A strong development of new knowledge and models, which may help to predict the risk of individual astronauts, is an absolute requirement in this field. Genetically tractable animal models offer unique opportunities to directly investigate the genetic and molecular events that may affect the biological response to GCR and related radiation.